2022
DOI: 10.1186/s13072-022-00457-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple epigenetic factors co-localize with HMGN proteins in A-compartment chromatin

Abstract: Background Nucleosomal binding proteins, HMGN, is a family of chromatin architectural proteins that are expressed in all vertebrate nuclei. Although previous studies have discovered that HMGN proteins have important roles in gene regulation and chromatin accessibility, whether and how HMGN proteins affect higher order chromatin status remains unknown. Results We examined the roles that HMGN1 and HMGN2 proteins play in higher order chromatin structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Furthermore, an additional study found enrichment in the occupancy of HMGN1 and HMGN2 in the areas of super-enhancers, defined as the areas containing a high density of H3K27ac and H3K4me1, in mouse ESCs, MEFs, and resting B cells [ 127 ]. In line with this, a very recent report [ 128 ] showed that HMGN1 and HMGN2 occupy compartment A (a transcriptionally active nuclear compartment) through their preferential binding to acetylated nucleosomes [ 128 ]. While HMGN1 depletion does not alter the higher-order chromatin structure, HMGNs are specifically localized to the cell-type-specific promoters and enhancers and promote transcription factor accessibility to these open chromatin areas, which form looping interactions, thus contributing to cell type-and stage-distinct gene expression [ 128 ].…”
Section: Introductionmentioning
confidence: 66%
“…Furthermore, an additional study found enrichment in the occupancy of HMGN1 and HMGN2 in the areas of super-enhancers, defined as the areas containing a high density of H3K27ac and H3K4me1, in mouse ESCs, MEFs, and resting B cells [ 127 ]. In line with this, a very recent report [ 128 ] showed that HMGN1 and HMGN2 occupy compartment A (a transcriptionally active nuclear compartment) through their preferential binding to acetylated nucleosomes [ 128 ]. While HMGN1 depletion does not alter the higher-order chromatin structure, HMGNs are specifically localized to the cell-type-specific promoters and enhancers and promote transcription factor accessibility to these open chromatin areas, which form looping interactions, thus contributing to cell type-and stage-distinct gene expression [ 128 ].…”
Section: Introductionmentioning
confidence: 66%
“…Transcriptional changes during white adipocyte browning are associated with changes in the epigenetic landscape, especially histone acetylation of H3K27 at cell-type-specific enhancers 29 31 . Given that the HMGN proteins colocalize with H3K27ac and modulate the levels of H3K27ac at cell-type-specific enhancers and stabilize cell identity 8 , 32 , 33 , we tested whether HMGNs alter H3K27ac levels during white preadipocyte differentiation into brown-like adipocytes. ChIP analyses of cultured white preadipocytes showed numerous differences in acetylation levels between WT and DKO preadipocytes at day 0 and 6 of preadipocyte differentiation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HMGN are chromatin architectural proteins ubiquitously expressed in all vertebrate cells and are known to bind to chromatin without DNA sequence specificity. Previous studies revealed that HMGN proteins modulate chromatin accessibility, transcription factor binding, and promoter–enhancer interactions, and they stabilize cell identity (He et al 2018; Garza-Manero et al 2019; He et al 2022; Zhang et al 2022). We now use Hmgn1 –/– ; Hmgn2 –/– double-knockout (DKO) mice to explore whether HMGN proteins regulate ameloblast differentiation.…”
Section: Introductionmentioning
confidence: 99%